Preparation of activated carbon from paper mill sludge waste activated by superheated steam - Siajam, Shamsul Izhar; Zainuddin, Halimatun Sakdiah; Sabli, Nordin; Yeow, Wen Feng; Yoshida, Hiroyuki (Inderscience Publishers, 2025)
Activated carbon was produced by treating dehydrated paper pulp with superheated steam in a rotary kiln. The activated carbon was analyzed for its physical properties and adsorption capacity in relation to the activation temperatures. Carbonization was conducted at 400°C, followed by activation between 600–900°C for 1 hour. Methylene blue was used to evaluate the adsorption performance. The activated carbon activated at 700°C exhibited 96% adsorption performance. The performance was attributed to the promoted pore development that prevented unnecessary burning by excluding oxygen. As a result, activated carbon with a high BET surface area (130 m2/g) and the presence of O-containing functional groups were confirmed by FTIR analysis. Thus, activation processes via superheated steam enhanced activated carbon physicochemical properties, making steam an excellent method to produce a promising adsorbent for utilizing paper pulp.